Comparing Alternative Jet Fuel Dependencies Between Combustors of Different Size and Mixing Approaches - Boehm, Randall C.; Colborn, Jennifer G.; Heyne, Joshua S. (Frontiers in Energy Research, 2021)
The current process for qualification of sustainable alternative jet fuels requires thousands of gallons of fuel and multiple levels of testing, which can take years to complete. To streamline this process, nearly twenty fuels were evaluated across approximately a dozen rigs to evaluate the relative ignition and lean blowout performance for fuels with different compositions and properties. Eight of nine rigs at ambient and elevated temperature conditions showed correlations with the derived cetane number for lean blowout. The remaining rig, the combustor of an auxiliary power unit, correlated most strongly with physical properties and a reference rig at chilled temperatures. In congregate, these lean blowout results illuminated two distinct regimes controlled by either the ease at which a spray breaks up or a fuel auto-ignites at a given operating condition. Similarly, multiphase ignition performance across rigs showed similar correlations to fuel properties. Here it is shown that (1) spray break-up and chemical processes timescales determine relative fuel performance trends across nearly 10 rigs, (2) a reference rig, such as the Referee Rig, can capture fuel performance trends of all rigs and engines evaluated to date by tailoring the inlet air and fuel temperatures, and (3) the Referee Rig is a viable tool for screening and evaluating sustainable alternative fuel candidates. References: [1] Peiffer, E.E., Heyne, J.S., and Colket, M., “Sustainable Aviation fuels Approval Streamlining: Auxiliary Power Unit Lean Blowout Testing,” AIAA Journal, Vol. 57, No. 11, November 2019, pp. 1-9